Brief considerations on the acquisition of works of art in the European regulation of public contracts - Pierpaolo Forte (Revista de Estudios de la Administración Local y Autonómica, 2017)
The work, renouncing to a precise definition of art, acknowledges that there are art objects and cultural objects, which, in this way, are relevant also in legal terms, and try to advance some reflections on the relevance of art in relation to the European discipline of public contracts and, in particular, what can be deduced from Directive 2014/24 / EU, which can well be understood as a sort of cultural sign that can provide insights into how art is perceived in Europe, even in political terms, in this historical phase. The paper therefore examines the use of negotiated procedures without prior publication of a contract notice, for the «creation or acquisition of a unique work of art or artistic performance», and to do so faces the problem of the object of the procurement by “contracting authorities” which deals with things or performances (works, supplies or services) relating to artistic products, by examining the needs which a public administration may have in relation to obtaining the availability of a work of art, and the different modes of this type of acquisition. Finally, the study examines the theme of «art exhibitions», trying to prove that they are autonomous objects, which are represented in the European directive under the diction «artistic performance».